Foreign subsidiaries as vehicles of industry 4.0: The case of foreign subsidiaries in a post-transition economy. Issue 6 (December 2021) - Jankowska, Barbara; Götz, Marta; Tarka, Piotr
Highlights: The strategy adopted by the HQ of a MNE impacts the possibility of foreign subsidiaries to act as vehicles of I4.0 transformation in host economies. The embeddedness in local environment guarantees the transition of knowledge from foreign subsidiaries to host market entities, whereas the innovation capacity of a foreign subsidiary does not seem to play any role. The industrial background of an FS and the FDI entry mode – greenfield or acquisition may strengthen or weaken the identified interdependencies. Abstract: We ask whether foreign subsidiaries may work as entities that neutralize the threat of marginalization of the post-transition economies in terms of Industry 4.0 (I4.0) adoption. Building on a conceptual model of foreign subsidiaries as I4.0 vehicles, we conducted interviews with 440 foreign subsidiaries from the manufacturing sector established in Poland. The originality of the paper concerns three key issues. First, our study shows that the strategy adopted by the headquarters is critical, as it impacts the possibility of foreign subsidiaries to act as vehicles of I4.0 transformation in host economies. Second, embeddedness in local environment guarantees the transition of knowledge, whereas the innovation capacity of a foreign subsidiary does not seem to play any role. Third, we focus on foreign subsidiaries established in a post-transition economy. The results of our research enrich the literature on types of foreign subsidiaries in transmitting and diffusing the knowledge received from headquarters and expose the prominent role of links with host market entities.